2017
DOI: 10.1080/19420889.2017.1325049
|View full text |Cite
|
Sign up to set email alerts
|

Social information use in threat perception: Social buffering, contagion and facilitation of alarm responses

Abstract: Group living animals can use the behavior of others as cues for the presence of threat in the environment and adjust their behavior accordingly. Therefore, different social phenomena that modulate the response to threat, such as social buffering, social transmission (contagion), and facilitation of alarm responses can be seen as different manifestations of social information use in threat detection. Thus, social phenomena that are functionally antagonistic, such as social buffering and social transmission of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Studies have demonstrated that group housed zebrafish recover more quickly from fin clipping than those held individually [76] and that fear responses are reduced when zebrafish have olfactory and more importantly visual cues of conspecifics [77,78]. This phenomenon is termed social buffering where social support assists in reducing responses to threatening stimuli or events and appears evolutionarily conserved from fish to mammals [77,78]. Thus, it is conceivable that if we repeated these experiments in group housed zebrafish we may see a lesser or no change in the complexity of movement.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that group housed zebrafish recover more quickly from fin clipping than those held individually [76] and that fear responses are reduced when zebrafish have olfactory and more importantly visual cues of conspecifics [77,78]. This phenomenon is termed social buffering where social support assists in reducing responses to threatening stimuli or events and appears evolutionarily conserved from fish to mammals [77,78]. Thus, it is conceivable that if we repeated these experiments in group housed zebrafish we may see a lesser or no change in the complexity of movement.…”
Section: Discussionmentioning
confidence: 99%
“…A powerful model of collective behavior is zebrafish shoaling, a form of affiliation with conspecifics that facilitates predator avoidance, foraging and stress coping (3,18,19). Mutual 10 attraction among zebrafish develops between ten to twenty days of age when an increasing fraction of swim steering events become socially biased towards neighboring fish and animals maintain a preferred distance from one another (17,20,21).…”
Section: Main Textmentioning
confidence: 99%
“… SUMMARY Social cues of threat are widely reported [13], whether actively produced to trigger responses in others, such as the emission of alarm calls, or by-products of an encounter with a predator, like the defensive behaviors themselves, such as an escape flight [414]. Although the recognition of social alarm cues is often innate [1517], in some instances it requires experience to trigger defensive responses [4,7].…”
mentioning
confidence: 99%